2019
DOI: 10.1111/1462-2920.14709
|View full text |Cite
|
Sign up to set email alerts
|

The biological role of the enigmatic C3larvinAB toxin of the honey bee pathogenic bacterium Paenibacillus larvae

Abstract: Summary Paenibacillus larvae is the causative agent of the notifiable epizootic American foulbrood, a fatal bacterial disease of honey bee larvae. The species P. larvae has been classified into four differentially virulent and prevalent genotypes (ERIC I‐IV), which also differ in their virulence factor equipment. Recently, a novel P. larvae toxin, the C3‐like C3larvin, has been described. Genome analysis now revealed that the C3larvin gene is actually a part of a toxin locus encompassing two genes encoding a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 72 publications
(149 reference statements)
1
25
0
Order By: Relevance
“…Consistent with this observation, P. larvae ERIC I and ERIC II gene inactivation mutants lacking C3larvin trunc expression did not cause larval mortality compared with WT strains when used for experimental infection [39]. These data suggested that despite its enzymatic activity in biochemical assays [38], C3larvin trunc does not influence the virulence of P. larvae [39]. Further in silico analyses then revealed that in P. larvae ERIC I and ERIC II, the C3larvin trunc gene is part of a binary AB toxin locus which had been annotated as non-functional due to several disruptions of the open-reading frames coding for the A-and B-subunits [34].…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…Consistent with this observation, P. larvae ERIC I and ERIC II gene inactivation mutants lacking C3larvin trunc expression did not cause larval mortality compared with WT strains when used for experimental infection [39]. These data suggested that despite its enzymatic activity in biochemical assays [38], C3larvin trunc does not influence the virulence of P. larvae [39]. Further in silico analyses then revealed that in P. larvae ERIC I and ERIC II, the C3larvin trunc gene is part of a binary AB toxin locus which had been annotated as non-functional due to several disruptions of the open-reading frames coding for the A-and B-subunits [34].…”
Section: Introductionsupporting
confidence: 73%
“…However, C3larvin trunc was shown to lack N-terminal sequences responsible for cell-entry activity, and indeed, the toxin was unable to invade mouse macrophages [38]. Consistent with this observation, P. larvae ERIC I and ERIC II gene inactivation mutants lacking C3larvin trunc expression did not cause larval mortality compared with WT strains when used for experimental infection [39]. These data suggested that despite its enzymatic activity in biochemical assays [38], C3larvin trunc does not influence the virulence of P. larvae [39].…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations